Sedentary Behavior of Elementary School Students During the Covid-19 Pandemic - Dwi Rizky Aditia Putra; Anira Anira (Universitas Pendidikan Indonesia, 2022)
Restrictions on social activity due to the Covid-19 pandemic had an impact on sedentary behavior. The purpose of this study was to investigate the physical fitness and sedentary behavior of elementary school students. The method of this study used quantitative descriptive research. The sampling technique used in this study was the total sampling. This study involved 89 students (male = 46; female = 43) as the samples. The instrument used in this study was the Adolescent Sedentary Activity Questionnaire (ASAQ). The data analysis employed the Microsoft Office Excel 2016 computer program. Based on the results of the research, sedentary behavior of the samples on weekdays (11 hours 45 minutes) and weekends (8 hours 49 minutes) were in the high category. This condition is concerning because it can cause many health problems in children. This research can be a reference for teachers to play a role in cultivating a healthy and active lifestyle. Researchers, for further research, are suggested to expand the size of the sample and update the instrument to gain more comprehensive results.